2021
DOI: 10.3390/jcm10061290
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease Is Associated with Increased Vulnerability of Coronary Atheromatous Plaques in Patients Undergoing Coronary Computed Tomography Angiography—Results from the Atherodent Study

Abstract: The present study aimed to investigate the link between the severity of periodontal disease (PD), coronary calcifications and unstable plaque features in patients who underwent coronary computed tomography for unstable angina (UA). Fifty-two patients with UA, included in the ATHERODENT trial (NCT03395041), underwent computed tomographic coronary angiography (CCTA) and dental examination. Based on the median value of the periodontal index (PI), patients were assigned to the low periodontal index (LPI) group (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The oral-health-related quality of life in patients with chronic diseases is a current discussion topic [ 65 ] including patients with cardiovascular disease and a relationship between periodontal and cardiovascular disease has been assessed in several studies [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oral-health-related quality of life in patients with chronic diseases is a current discussion topic [ 65 ] including patients with cardiovascular disease and a relationship between periodontal and cardiovascular disease has been assessed in several studies [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Gomes-Filho et al (2020), who proved that the PD severity is strongly associated with the risk of developing an ACS (two to four times higher risk) [20]. Similar results were obtained in the ATHERODENT trial, an Angio-CT based study that investigated the correlation between PD and CT features of vulnerable atheromatous plaques, and revealed a direct link between PD severity, atherosclerosis and coronary plaque vulnerability in patients with unstable angina (UA) [ (21]. Thus, it was observed that in patients with high-risk plaques (that contain at least two of the following vulnerability features: napkin ring, spotty calcification, low attenuation atheroma and positive remodeling), the PD was more severe compared with those without VP (28.20 ± 13.34 vs. 18.71 ± 11.31, p = 0.001).…”
Section: Periodontal Disease-the Local Inflammatory Disease Increasing Cardiovascular Riskmentioning
confidence: 63%
“…Moreover, a higher calcium score was identified in patients with PD, especially in those with severe forms (p = 0.0001). The gingival indices most frequently associated with ACS in the ATHERO-DENT trial were papillary bleeding index (4.5 ± 3.06 vs. 2.04 ± 1.96, p = 0.002) and clinical attachment loss, an irreversible sign of PD (3.6 ± 2.91 vs. 1.66 ± 1.8, p = 0.009) [21].…”
Section: Periodontal Disease-the Local Inflammatory Disease Increasing Cardiovascular Riskmentioning
confidence: 97%
“…The risk of carotid artery calcification was significantly higher by 102% in patients with PD (OR = 2.02; 95% CI: 1.18–3.45) [ 104 ]. It is also worth mentioning that the study by Rodean et al showed that the occurrence of PD was associated with a higher risk of the presence of high-risk atherosclerotic plaques in the coronary arteries [ 105 ]. In a study by Cowan et al including 8092 participants who were followed for an average of 12.9 years, PD was shown to independently increase the risk of venous thromboembolism by 29% (HR = 1.65; 95% CI: 1.25–2.18), with this association it weakened because confounding factors were taken into account [ 106 ].…”
Section: Periodontal Disease and Risk Of Atherosclerosis Cardiovascul...mentioning
confidence: 99%